Barriers and enablers of digital transformation: an exploratory analysis of digital debt and devops - Oliveira, Thiago Carlos de Sousa (2022)
The rapid diffusion of digital technologies, combined with a large amount of data generated by interactions between users and organizations, has led to the reinvention of the way in which markets develop and improve their business models. It is not uncommon to hear that every company is a technology company. However, this status cannot be achieved quickly as it requires the development of organizational resources and capabilities, in addition to a new digital mindset to produce a strategy capable of overcoming its internal barriers and leveraging the enablers of this transformation. Incumbent and established organizations present barriers to their digital transformation when facing constraints from their legacy systems with their needs for modernization or even replacement. Furthermore, the pressure to deliver new business value propositions forces sub-optimal technical decisions that take a toll on product quality and the flexibility of the solutions. This accumulation of deficiencies in the organization's technological portfolio promotes digital debt with its customers, undermining its value proposition. In view of this, new philosophies, such as DevOps, have been emerging to ensure a cycle of continuous improvement, increase productivity, address product quality issues, change the culture, and adopt new approaches to deliver digital products. This exploratory study presents evidence that digital debt and DevOps act, respectively, as a barrier and enabler of the organization's digital maturity, promoting a discussion about their prioritization in the organization's digital business strategy. A proposal for deepening the academic field is also presented.